PEMBERDAYAAN PEREMPUAN MELALUI PEMBUATAN KERUPUK DAUN KOPI PADA MASYARAKAT DESA HARJOMULYO KECAMATAN SILO KABUPATEN JEMBER - Novita Mayasari; Hety Mustika Ani (Economic Education, University of Jember, 2015)
The empowerment through training of the making of coffee leaf cracker to women is a training which is designed to improve the skill and creativity in order to have productive activities for women. This study is aimed to describe the process and to know the impact of the empowerment of the women in the village of Harjomulyo Silo subsdistrict Jember District which is conducted through the making of coffee leaf crackers. The approach used in this study is an action research to the type of participatory action research. This research is determined using the method of purposive area, precisely is in the Harjomulyo village Silo Subdistrict Jember District. The determination of the research subject used purposive sampling method. The subject of this research is women who work as labor and the owners of coffee plantation independently. This empowerment is implemented through four stages, namely diagnosing, action planning, taking action and evaluating action. There are three impacts of women's empowerment in Harjomulyo Village Silo Subdistrict Jember District which is conducted through the making of coffee leaf crackers, namely the utilization of the coffee leaves trimming, an increasing of the productivity of women after the coffee harvest season ends and the additional income if coffee leaf crackers are sold. The process and the impact of empowerment through training in the making of coffee leaf crackers run well according to the criteria of success that has been established it can be seen from the results of the evaluation process and, the impact of the evaluation instrument of empowerment by research subjects who gave a positive response on this evaluation